The Same Oxidation‐State Introduction of Hypervalent Sulfur via Transition‐Metal Catalysis - Wang, Ming; Jiang, Xuefeng (Chemical record, 2021)
Sulfonyl compounds have attracted considerable interest due to their extensive applications in drug discovery, agricultural, and material science. The access to the assembly of SO2‐containing compounds via the same oxidative‐state introduction of hypervalent sulfur has come to the fore in the recent years. Especially, the transition‐metal‐involved synthesis of hypervalent sulfur compounds is the most effective strategy since SO2 is easy to insert into the metal‐carbon bonds. This review discusses the application of the same oxidation‐state introduction of hypervalent sulfur strategy under the transition‐metal‐catalyzed conditions, and presents according to different metal catalysts and the synthesized diversity hypervalent sulfur‐containing compounds skeletons, including sulfonamides, sulfones, sulfinamides, sulfonyl acids and sulfonyl fluorides. This review discusses the application of the same oxidation‐state introduction of hypervalent sulfur strategy under the transition‐metal‐catalyzed conditions.